Penyuluhan dan Pelatihan Pendaftaran Surat Izin Usaha Mikro Kecil (IUMK) - Ella Anastasya Sinambela; Rahayu Mardikaningsih; Eli Retnowati; Utami Puji Lestari; Jahroni Jahroni; Arif Rachman Putra; Misbachul Munir; Didit Darmawan; Samsul Arifin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The community chooses to open a small business as an economic activity. MSMEs provide many benefits for the state and society. MSMEs can provide high income for the country and create jobs for the community. For this reason, the government provides assistance as support to MSME actors. However, not all MSME actors can receive government assistance because they do not have a permit. PkM activities are carried out to help the community with the knowledge possessed by the PkM team as academics. The purpose of the PkM activities being carried out at this time is to help MSME actors who do not have a business license to register their business. PKM activities were carried out in Tropodo Waru Village, Sidoarjo. PkM activities were attended by 35 MSME actors. The implementation of the activity ran smoothly with a few obstacles caused by weather conditions. Positive support was obtained by the PkM team from the village, MSME actors, and Sunan Giri University. PkM activities are also used as a means to build good relations from Sunan Giri University in Surabaya to the community, especially in Tropodo Village.